'It's like being in bubbles': affordances and challenges of virtual learning environments for collaborative learning in interpreter education. Issue 3 (2nd July 2020) - Braun, Sabine; Davitti, Elena; Slater, Catherine
ABSTRACT: We report on a study evaluating the educational opportunities that highly multimodal and interactive Virtual Learning Environments (VLE) provide for collaborative learning in the context of interpreter education. The study was prompted by previous research into the use of VLEs in interpreter education, which showed positive results but which focused on preparatory or ancillary activities and/or individual interpreting practice. The study reported here, which was part of a larger project on evaluating the use of VLEs in educating interpreters and their potential clients, explored the affordances of a videoconferencing platform and a 3D virtual world for collaborative learning in the context of dialogue interpreting. The participants were 13 student-interpreters, who conducted role-play simulations in both environments. Through a mix of methods such as non-participant observation, reflective group discussions, linguistic analysis of the recorded simulations, and a user experience survey several dimensions of using the VLEs were explored including the linguistic/discursive dimension (interpreting), the interactional dimension (communication management between the participants), the ergonomic dimension (human-computer interaction) and the psychological dimension (user experience, sense of presence). Both VLEs were found to be capable of supporting situated and autonomous learning in the interpreting context, although differences arose regarding the reported user experience.